RELEVANSI BUDIDAYA RAMAH LINGKUNGAN TERHADAP PERLINDUNGAN LAMUN SKALA LOKAL DI PESISIR LOMBOK TIMUR - Abdul Syukur; Mahrus Mahrus; Syachruddin AR (Postgraduate, University of Mataram, 2019)
The environment in coastal areas is currently undergoing a process of exploitation, and in some locations the condition of natural resources is already at a critical point. This research is designed to make eco-friendly cultivation model as a small-scale fisherman livelihood supplement and local seagrass protection strategy. The virtues of this research include three aspects: (1) environmental aspect, (2) economic aspect of small fisherman and (3) social aspect in creating value of togetherness among community member in study location. Taking research data using direct observation method, interview and in-depth discussion. Respondents in this research are fishermen and fishermen caught fishermen group that catch fish around the seagrass area. Further data obtained before the analysis is validated through in-depth discussion. Data analysis using discrete statistic method. The results showed that environmentally friendly cultivation has become the livelihood of fishermen in the study location, and they get additional income of Rp. 7,500. 000 within a period of cultivation (6-7 months). In addition, they earn additional income of Rp. 200,000 from fishing service by utilizing the means of cultivation (KJA). Furthermore, the farmer's fishermen are aware of the negative effects of the utilization that are disruptive from the use of bombs and potassium to cultivation and they play an active role in preventing it. In this case, smallholder cultivation has relevance in seagrass habitat protection and can be considered in the policy of empowering fisherman's economy and conservation of local coastal environment outside conservation area. Keywords: Value of eco-friendly cultivation, small Nealayan and Local scale seagrass protection